Optimization of hot water extraction of roselle juice using response surface methodology: a comparative study with other extraction methods - Wong, Peng‐Kong; Yusof, Salmah; Ghazali, Hasanah; Che Man, Yaakob (Wiley, 2003)
Roselle has regained the attention of many fruit juice manufacturers in Malaysia as a product that contains high ascorbic acid and anthocyanins. However, ascorbic acid and anthocyanin pigments can be easily destroyed during processing of fruit juice. Therefore, in the present study, the effects of different processing methods, namely hot water extraction (HWE), hot water blending, cold water blending and screw press, on the changes in anthocyanins and ascorbic acid contents of roselle juice were evaluated. The anthocyanins and ascorbic acid contents of roselle were determined using the pH differential method and high‐performance liquid chromatography respectively. The physico‐chemical characteristics and sensory properties of roselle juice were also evaluated. The results of the study indicate that the HWE method is the most effective extraction method, resulting in high anthocyanins and ascorbic acid contents of 43 g l−1 (as delphinidin‐3‐glucoside) and 2.34 g kg−1 respectively. The optimum juice extraction conditions were 3.5 h at 60 °C. Copyright © 2003 Society of Chemical Industry